Characterization of organic composts produced by family farming for lettuce cultivation - Bertani, Rosemary Marques de Almeida; Arruda, Maria Cecília de; Deus, Angélica Cristina Fernandes [UNESP]; Fischer, Ivan Herman; Rossi, Renan; Maganhã, Carlos Augusto (Lepidus Tecnologia, 2022)
Organic composts can be sustainably used for lettuce production in family farming by employing residues from the farm itself through composting. For an efficient and safe use of these wastes, monitoring the composting process and adopting good agricultural practices is necessary to produce safe food. Therefore, the objective of the present study was to identify and quantify pathogenic microorganisms, as well as to evaluate the chemical characteristics of organic composts and their effects on organic lettuce production. Six lettuce production cycles were studied, in which organic composts produced at the farm were used for planting and topdressing fertilization. Composting was carried out according to the method of revolved windrows, using crop remains, leaves and cattle manure. The results obtained for fresh mass and chemical analyses of composts, soil and plant were qualitatively compared. For microbiological analyses, results were evaluated according to current legislation. The composition of the used material and management of the composting process affected the chemical characteristics of organic composts to be applied to the soil. The organic compost used in each cycle was efficient for plant nutrition, except boron supply. Presence of thermotolerant coliforms was above the maximum acceptable limit, indicating contamination of the compost. In most cycles, the organic compost did not undergo proper composting. Using organic composts proved to be a sustainable alternative for organic lettuce production in family farms, but the present study indicated the need for technical training.
Keywords: composting; good agricultural practices; microorganism; organic cultivation